Crime management strategy for specialist theft crimes in housing in pangkalpinang city: Policy evaluation and implementation - Huda, Khairul; Rachmadhika, Galang; Dennis, Gilbert Rayi; Sari, Patricia Widya (The International Journal of Politics and Sociology Research, 2025)
This research will review the Strategy for Combating Specialist Theft Crimes in Housing in Pangkalpinang City, with a focus on Policy Evaluation and Implementation. Residential burglary has become a significant issue that disrupts public safety in Pangkalpinang City. This research aims to conduct an in-depth analysis and evaluation of policies, implementation of more effective strategies, the level of theft crime in Pangkalpinang City can be suppressed, thus creating a safe and comfortable environment for the community. This research uses a qualitative research method with a case study approach, which involves interviews with police officers, housing security, and the local community. The results illustrate that although there have been policies set by the Government and law enforcement officials, implementation in the field still faces various challenges, including a lack of coordination between institutions, limited resources, and minimal community participation in maintaining environmental security. In addition, the strategies implemented are still reactive rather than proactive. The research proposal includes increasing cooperation between the police and the community, strengthening the security patrol program, as well as counseling on theft prevention measures for residential residents of Pangkalpinang City.